Properties and Bounds of Jensen-Type Functionals via Harmonic Convex Functions. (9th August 2021) - Mughal, Aqeel Ahmad; Almusawa, Hassan; Haq, Absar Ul; Baloch, Imran Abbas
Abstract : Dragomir introduced the Jensen-type inequality for harmonic convex functions (HCF) and Baloch et al. studied its different variants, such as Jensen-type inequality for harmonic h -convex functions. In this paper, we aim to establish the functional form of inequalities presented by Baloch et al. and prove the superadditivity and monotonicity properties of these functionals. Furthermore, we derive the bound for these functionals under certain conditions. Furthermore, we define more generalized functionals involving monotonic nondecreasing concave function as well as evince superadditivity and monotonicity properties of these generalized functionals.